Prediksi Kekuatan Otot Pada Kegiatan Lifting - Susilo, Stephanus (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
There must be a lot of factors influence human muscle strength, both internal and external aspects. This study considers three main factors thought to affect human muscle strength, which are: muscle contraction, types of hand, and also gender. There are also covariance variables that are used, e.g. BMI and physical activity. Strength of biceps, forearms and trapezius muscles were measured using experimental design approach, among individuals with range of aged 19-24 years. Based on the calculation, all factors are proven to have significant correlation at significance level 0f 0.05. In addition, BMI and activity also has a relationship with muscle strength.Using all these factors, regression linear model was built to predict muscle strength. Additionally, maximum lifting strength was also estimated based on predicted muscle strength. Based on internal validity using paired t-test, the result show that predicted muscle strength and maximum lifting force have no difference to measured ones